Differences in Vestibular-Evoked Myogenic Potential Responses by Using Cochlear Implant and Otolith Organ Direct Stimulation - Rodriguez Montesdeoca, Isaura; Ramos de Miguel, Angel; González, Juan Carlos Falcon; Barreiro, Silvia Borkoski; Pérez Fernández, Nicolás; Vanspauwen, Robby; Ramos-Macias, Angel (Frontiers in Neurology, 2021)
Objective Several studies have demonstrated the possibility to obtain vestibular potential elicited with electrical stimulation from cochlear and vestibular implant. The objective of this study is to analyze the vestibular evoked myogenic potential(VEMPS) responses obtained from a group of patients implanted with cochlear and vestibular implant. Material Method We compared two groups: in the first group 4 cochlear implant (CI) with acoustic cVEMPS response before CI surgery, and in the second group 3 patients with no bilateral cVEMPS responses preoperatively and bilateral vestibular dysfunction which received unilateral Vestibular implant (Cochleo-Vestibular electric stimulation) were included in this study. We analyze the electrically elicited cVEMPS in all patients after stimulation with cochlear and vestibular electrode array stimulation. Results We present the results obtained postoperatively in both groups. Presence of electric cVEMPS responses were observed in all patients with vestibular direct stimulation with P1 and N1 latencies were in 11,33-13,6 and 18,3-21 ms. In CI patients, electric cVEMPS were present only in one of the subjects with cochlear implant cross stimulation andP1 and N1 latencies were 9,67 and 16,33. In these patients, the responses present shorter latencies than acoustically. Conclusions Electrically cVEMPS can be present after cochlear and vestibular stimulation, and suggest stimulation of vestibular elements, although clinical effect must be further studied.